Synergistic Effect of Bimetallic Sulfide Synthesized by a Simple Solvothermal Method for High-Efficiency Oxygen Evolution Reaction - Zou, Zhengguang; Wang, Qian (Energy & fuels, 2021)
The energy consumption of water electrolysis mainly comes from anode oxygen evolution reaction (OER) because of its sluggish four-electron transport processes. It is significant to fabricate an efficient OER electrocatalyst for water electrolysis. In this work, bimetallic sulfide nanoparticles (FeNiSs) are prepared by a facile solvothermal method as an OER catalyst. Benefiting from its small particle size and synergistic effect of iron and nickel, this transition-metal sulfide has an excellent catalytic performance for OER. It only needs overpotentials of 223 and 286 mV to achieve current densities of 10 and 100 mA cm–2 with an extremely low load of 0.21 mg cm–2 on noble electrode glassy carbon, respectively. Furthermore, the Tafel slope of 38.2 mV dec–1 is also extremely low, which means its fast electron transport during OER. Also, it could work as an OER electrode for 100 h without obvious degeneration, which indicates the superb durability. In addition, this facile solvothermal method and synergistic effect can enlighten researchers to explore and develop other efficient and robust electrocatalysts for energy conversions.